Design and development of medical electronic instrumentation : a practical perspective of the design, construction, and test of medical devices - Prutchi, David (Wiley-Interscience, 2005)
Annotation Design and Development of Medical Electronic Instrumentation fills a gap in the existing medical electronic devices literature by providing background and examples of how medical instrumentation is actually designed and tested. The book includes practical examples and projects, including working schematics, ranging in difficulty from simple biopotential amplifiers to computer-controlled defibrillators. Covering every stage of the development process, the book provides complete coverage of the practical aspects of amplifying, processing, simulating and evoking biopotentials. In addition, two chapters address the issue of safety in the development of electronic medical devices, and providing valuable insider advice.
Keywords: Medical instruments and apparatus -- Design and construction.; Medical electronics -- Design and construction.; Amplifiers (Electronics); Biomedical engineering.; Electrophysiology.; Patient monitoring -- Equipment and supplies.; elektronické knihy; electronic books